AN ANTHOLOGY OF THE DISTINGUISHED ACHIEVEMENTS IN SCIENCE AND TECHNIQUE. PART 52: ROCKET-SPACE TECHNOLOGY DESIGNER MIKHAIL YANGEL AND HIS ACCOMPLISHMENTS IN MISSILE DESIGN - M. I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2019)
Purpose. Preparation of short scientifically-historical essay about the distinguished designer of domestic |space-rocket technique and one of basic creators of missiles for a Soviet rocket-nuclear «shield» Mikhail Kuzmich Yangel. Methodology. Known scientific methods of collection, analysis and analytical treatment of scientific and technical information, regarding becoming and development in the USSR of space-rocket technique of the military and peaceful applications and resulted in scientific monographs, journals and internet-reports. Results. A short scientifically-historical essay is resulted about the distinguished Soviet designer of space-rocket technique of M.K. Yangel, becoming one of creators of domestic strategic rocket-nuclear «shield». Basic scientific and technical achievements of talented and purposeful scientist-mechanic M.K. Yangel are described, becoming in 1954 Head and Chief Designer of the Special Designer Bureau No. 586 (SDB-586, Dnepropetrovsk city), in area of development and creation of powerful battle ballistic rockets of the strategic applications and missiles for the peaceful mastering of space. It is shown that under scientific guidance of the Chief Designer of SDB-586 (in 1966 it began to be named DB «Southern») M.K. Yangel in the USSR were developed and accepted on the armament of rocket strategic armies the Soviet army: battle strategic rockets of the first generation (rockets with military indexes 8K63, 8K65 and 8K64); battle intercontinents ballistic rockets (ICBR) of the second (rockets with military indexes 8K67, 8K69 and 8К67П) and the third (rockets with military indexes 15A14 (on terminology of NATO SS-18 «Satan»), 15A15, 15A16 and 15A18) generations. At creation in the USSR of battle ICBR of the fourth generation (rockets with the military indexes of 15А18М, 15Ж60 and 15Ж61) the ideas of M.K. Yangel were applied. These battle ICBR provided in the period of the «Cold War» for the USSR a party in the world race of strategic rocket-nuclear armaments. Powerful domestic missiles are «Space-1», «Space-2», «Cyclone-2» and «Cyclone-3», created at SDB-586 (DB «Southern») under the guidance of M.K. Yangel on the base of the indicated battle ICBR, executed the tasks laid on them in area of the peaceful mastering of space. Originality. Certain systematization is executed known from mass of scientific and technical materials media, regarding becoming and development in the USSR of rocket industry, having an important military-strategic and civil value. First for a wide reader the concrete contribution of SDB-586 (DB «Southern»), headed in the period of 1954-1971 by Academician of the Academy of Sciences of the Ukrainian SSR and the Academy of Sciences of the USSR M.K. Yangel is exposed in the concentrated kind, in creation of powerful Soviet battle ICBR, making in the period of 1959-1991 basis of rocket-nuclear «shield» of the USSR. Practical value. Scientific popularization and deepening for the students of higher school, engineering-technical and scientific workers of physical-technical knowledge in area of history of becoming and development in the former USSR of military and peaceful rocket production, extending their scientific and technical range of interests and further development of scientific and technical progress in society.